Development of versatile bio-stable oral polymeric delivery systems for proteins - Kondiah, Pierre Pavan Demarco (My University, 2015)
An oral proteomatrix drug delivery platform was formulated using pH responsive biostable polymers for slow release kinetics for the treatment of the neurodegenerative disease, multiple sclerosis (MS), which was the primary aim. After successful design and optimization for utilizing this system for MS, this system was further applied as a versatile platform for oral protein delivery. Interferon beta (INF- ) was selected as the oral treatment for MS. The fundamental effect of INF- in the treatment of MS is based on reducing the immune response that is directed against central nervous system myelin, i.e. the fatty sheath that surrounds and protects nerve fibers. Damage of nerve fibers, resulting in demyelination, consequently causes nerve impulses to be slowed or halted, thus producing symptoms of MS (Jongen et al., 2011). To date, INF- is effectively being used to treat MS subcutaneously or as intramuscular injections. These forms of administration have commonly been associated with multiple problems of pain, allergic reactions, poor patient compliance and chances of infection (Chiu et al., 2007). It was thus concluded to design an oral platform for the delivery of multiple protein therapeutic formulations. To prove the versatility of the proteomatrix system, two other demanding protein therapeutics for oral delivery, insulin and erythropoietin, were selected for further in vitro Box-Behnken series of formulations and in vivo analysis. By administration of these oral protein systems, a greater patient compliance can be achieved, thus enhancing the therapeutic profiles of patients with conditions of MS, diabetes and chronic renal failure resulting in chronic anemia. All studies consisted of in vitro drug release studies, characterization using specific analytical techniques for testing the mechanical properties, as well as the physicochemical characteristics of the copolymeric system. All proteins, INF- , insulin and erythropoietin, were analyzed in vivo using New Zealand White rabbits (NZW) with determination of the protein from serum obtained during regular blood sampling intervals.
Keywords: Drug Delivery Systems